Development Disparities in India: An Enquiry into Convergence - Banerjee, Arpita (Springer, 2015)
This book highlights the development disparities in India and considers three complex areas of development – economic wellbeing, human progress and agricultural development – over a period of forty years since the 1970s. The novelty of the book lies in is its rich analytical foundation and the use of sophisticated statistical and economic tools to determine the causes of socioeconomic disparity between Indian states. The trends of inequality, polarization and disparity are highlighted with regard to income, human development indicators and agricultural production and productivity. The book also identifies the factors underlying divergence in economic and social activity in India and provides policy suggestions for bringing about more balanced and inclusive development in India.